2020
DOI: 10.1080/2162402x.2020.1841935
|View full text |Cite
|
Sign up to set email alerts
|

Hist-Immune signature: a prognostic factor in colorectal cancer using immunohistochemical slide image analysis

Abstract: Computerized image analysis for whole-slide images has been shown to improve efficiency, accuracy, and consistency in histopathology evaluations. We aimed to assess whether immunohistochemistry (IHC) image quantitative features can reflect the immune status and provide prognostic information for colorectal cancer patients. A fully automated pipeline was designed to extract histogram features from IHC digital images in a training set (N = 243). A Hist-Immune signature was generated with selected features using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Certain quantitative signature of tumor-infiltrating immune cells is increasingly recognized as a predictive biomarker to enable personalized treatment selection and improve patient management ( 9 ). Although the potential clinical relevance of density and ratios of infiltrating cells has already been evaluated in previous studies ( 6 , 10 12 ), with the recent availability of high-throughput quantitative image features extracting algorithm ( 13 ), there is now an opportunity for the systematic analysis of immunohistochemistry (IHC) staining digital image to identify previously unrecognized features that correlate with patients’ prognoses ( 14 ). To the best of our knowledge, there were no prognostic models based on IHC-stained digital image analysis being developed to individually predict the survival outcomes in patients with resected NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Certain quantitative signature of tumor-infiltrating immune cells is increasingly recognized as a predictive biomarker to enable personalized treatment selection and improve patient management ( 9 ). Although the potential clinical relevance of density and ratios of infiltrating cells has already been evaluated in previous studies ( 6 , 10 12 ), with the recent availability of high-throughput quantitative image features extracting algorithm ( 13 ), there is now an opportunity for the systematic analysis of immunohistochemistry (IHC) staining digital image to identify previously unrecognized features that correlate with patients’ prognoses ( 14 ). To the best of our knowledge, there were no prognostic models based on IHC-stained digital image analysis being developed to individually predict the survival outcomes in patients with resected NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Therefore, alternative approaches have been explored to improve the prognostic accuracy of patients with colorectal cancer. 6,7 Tumor deposits (TDs) were incorporated into the American Joint Committee on Cancer (AJCC) TNM classification (eighth edition) and classified as pN1c (stage III) in the absence of lymph node metastasis. 5 However, recent studies have shown that TDs are associated with worse prognosis regardless of lymph node status.…”
mentioning
confidence: 99%
“…4,5 Therefore, alternative approaches have been explored to improve the prognostic accuracy of patients with colorectal cancer. 6,7…”
mentioning
confidence: 99%